(untitled) - Kahan, Seth (San Francisco, 2013)
Offers a framework of 7 key activities for results-driven innovation, from intelligence-gathering through execution * Goes beyond abstract advice to offer hands-on approaches that are relevant and applicable in any organization * The companion and follow-up to Seth Kahan's bestselling first book,Getting Change Right and FastCompany.com blog Leading Change Grounded in market-based reality, Getting Innovation Right is an indispensable resource for leaders looking to drive results and move in fresh directions.
Keywords: Leadership,Lãnh đạo